Aspects of the new repurchase system of monetary control in South Africa - Springfield, Samantha Claire (Rhodes University, Faculty of Commerce, Department of Economics, 2001)
The main objective of monetary policy is to protect the value of the currency, and in so doing, achieve the objectives of maximum economic growth, development, and the creation of employment opportunities. As from 1985, under the advice of the De Kock Commission, the South African Reserve Bank (SARB), implemented the classical cash reserve system of monetary control. Under this system, the SARB was willing to refinance the money market shortage fully, automatically, and on certain predetermined terms, conditions and costs. However, since the new political dispensation in 1994, South Africa's financial markets have become more globalized, liberalised, and integrated. Thus, the classical cash reserve system had lost its usefulness, and was no longer effective. As from March 1998, the SARB implemented the new repurchase system of monetary control. In implementing the repurchase system of monetary control, South Africa was adopting a more eclectic approach. This system is aimed at making monetary policy more effective and more flexible in a financial environment filled with complexities. This study finds that the repurchase system has thus far been successful in meeting its objectives. Interest rates are more flexible and sensitive to developments in the domestic and external environment, the signalling mechanism of the SARB has proved to be successful, accommodation and interest rates are closely related and the interbank market has become more developed. Therefore, the repurchase system appears to be more efficient than the previous system of monetary control in South Africa.
Keywords: Monetary policy -- South Africa; Credit control -- South Africa